Ester-Based Hydrophilic Cyclodextrin Nanosponges for Topical Ocular Drug Delivery - Hayiyana, Zikhona; E. Choonara, Yahya; Makgotloe, Aubrey; C. du Toit, Lisa; Kumar, Pradeep; Pillay, Viness (Current Pharmaceutical Design, 2016)
Background: Cyclodextrin-based nanosponges are hyper-cross-linked supramolecular architectures. Similar to the parent compound they are derived from, they have been shown to possess the ability to form inclusion and non-inclusion complexes with drugs of different polarities, enzymes, proteins, peptides and macromolecules. Cyclodextrins only form inclusion complexes with hydrophobic guest molecules, while nanosponges extend this function by forming inclusion and non-inclusion complexes with both hydrophobic and hydrophilic compounds. This host-guest interaction provides enhancement in stability, solubility and sometimes in membrane permeability. Objective: The potential of ester-based hydrophilic nanosponges as drug carriers in topical ocular drug delivery was assessed by undertaking drug loading, drug release, phase solubility and ex vivo pig corneal drug permeation studies on the nanosponges. Method: The ester-based cyclodextrin-based nanosponges were synthesized through cross-linking β-cyclodextrin by pyromellitic dianhydride. Various concentrations of pyromellitic dianhydride, the cross-linker, were initially tested for their effects on the drug loading capacity of the nanosponges. Thereafter, varying ratios of drug to nanosponge complexes were studied and analyzed for their drug release kinetics, and solubility and permeation effects. Results: A cyclodextrin-based nanosponge drug delivery system with potential to improve corneal permeation and drug solubility was formulated. Their ability to improve pig corneal permeation was shown; where up to 75% permeation of the model drug was achieved in the presence of the nanosponges as compared to the 28% permeation of the pure drug. The nanosponges provided drug release for approximately an hour. This is a common behavior for hydrophilic complexes due to their high solubility in aqueous media. Conclusion: The ester-based hydrophilic cyclodextrin-based nanosponge derivative can be used as a drug delivery system in topical ocular drug delivery, to improve stability, solubility and corneal permeation.
Keywords: membrane (corneal) permeation